Exploring Recruitment to Randomised Trials Within Current Clinical Care Pathways: A Qualitative Case Study - Emmanuel, Gloria (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2024)
Background: Randomised clinical trials constitute a cornerstone in the establishment of evidence-based healthcare practices (Hariton & Locascio 2018). Internationally, a positive correlation exists between the degree of research activity within a national health system and improved patient outcomes (Ozdemir et al. 2015, Jonker et al. 2020). Despite this, the execution of clinical trials frequently encounters challenges, characterized by missed targets, extensions, and recruitment failures (McDonald et al. 2006, Briel et al. 2021). The PRioRiTy study, a collaborative effort between the Health Research Board-Trials Methodology Research Network (HRB-TMRN) and the James Lind Alliance (JLA) in the United Kingdom, sought to address and prioritise key methodological questions aimed at enhancing recruitment to randomised trials (Healy et al. 2018). This pivotal initiative yielded a curated list of the top 10 priority recruitment questions, collectively addressing uncertainties surrounding the recruitment to randomised trials. Foremost among these uncertainties, is the paucity of empirical knowledge pertaining to the coexistence of randomised trials with existing clinical care pathways and the utilisation of clinical care pathways for the recruitment of participants into trials. Aim: To explore, understand and describe if, and how, current Clinical Care Pathways (CCPs) were being utilised for recruitment to randomised trials. Methods: The study employed a single instrumental case study design, aligning with the goal of exploring the use of CCPs for trial recruitment. The utility of CCPs were explored through a purposive selection of seven case trials in diverse clinical care pathways that were currently recruiting within a large acute care setting in Ireland. A multiple data collection method was employed, which included document analysis of Patient Information Leaflets (PILs) and trial protocols, Non-Participant Observations of trial recruitment and semi-structured interviews (n=25) with trial recruiters (n= 23) and trial participants (n=2) in relation to these seven case trials. The study data was holistically analysed using a Reflective Thematic Analysis (RTA) approach. Findings: The findings of this case study are thematically represented into four themes and 13 corresponding sub-themes that describes the utility of CCPs during the various phases of a trial recruitment process. The four overarching themes identified in this study were: 1) `CCPs as a conduit for initiating recruitment?; 2) `A parallel pathway approach for trial recruitment?; 3) `Complexities of recruitment - an issue beyond CCPs?; 4) `Factors affecting trial recruitment within CCPs?. Conclusion: The case study presented the various ways in which CCPs were utilised through the different phases of trial recruitment. CCPs were commonly used during the initial phase of trial recruitment, where potential participants were identified, pre-screened for eligibility, and introduced to the trial. However, CCPs were less commonly utilised during subsequent phases of trial recruitment including informed consent, screening, and randomisation due to the advanced requirements of tasks involved in these phases. The advanced requirements included the need for specialised facilities, focussed time and attention, and adherence to strict protocol timelines. In order to address these challenges, the subsequent recruitment processes diverged onto a parallel pathway that offered a purpose-built infrastructure and focused attention to potential trial participants. Although the parallel pathway approach benefitted the overall conduct of the trial recruitment process, avenues for further optimising the utility of CCPs for trial recruitment was identified. Key considerations for optimising the utility of CCPs for trial recruitment include expediting the development of a national healthcare records system to streamline sourcing of patient data for trial eligibility, appointment of clinician academics, securing protected research time, facilitating funding mechanisms, and enhancing the overall governance and infrastructural support. These enhancements could collectively contribute to a more streamlined and efficient trial recruitment process, addressing existing challenges and fostering a conducive environment for advancing evidence-based healthcare practices.
APPROVED
Keywords: Clinical trial recruitment; Randomised clinical trials; Clinical care pathways